Identification of PDGF Receptors on Human Megakaryocytes and Megakaryocytic Cell Lines - Yang, M; Khachigian, L M; Hicks, C; Chesterman, C N; Chong, B H (Thrombosis and Haemostasis, 1997)
Platelet-derived growth factor (PDGF) is a potent chemotactic and mitogenic factor implicated to play important roles in a variety of normal and pathophysiologic settings. We investigated PDGF receptor expression on human megakaryocytes and several megakaryocytic cell lines (CHRF, DAMI, Meg-01, M-07e) using enzyme-linked immunosorbent assay (ELISA), flow cytometry and immunocytochemical staining. Both PDGF receptor subtypes were identified on CHRF, DAMI, and Meg-01 cells by ELISA; PDGF beta-receptor levels exceeded alpha-receptor levels. Flow cytometry revealed that beta-receptor levels on CHRF and DAMI cells exceeded those on Meg-01 cells, and that M-07e expressed neither receptor. Immunocytochemical staining confirmed these findings and determined that bone marrow megakaryocytes also expressed PDGF receptors. Exposure of megakaryocytes to PDGF-BB dramatically induced the expression of the immediate-early gene, c-fos, within 30 min. Moreover, PDGF-BB significantly stimulated CHRF proliferation and colony formation. The present study demonstrates the presence of functional PDGF receptors on human megakaryocytes and their ability to mediate a mitogenic response.